Investigation of Cytotoxic Effects of Recombinant Human Interferon Lambda-1 and Its Pegylated Form on Human Conjunctival Epithelial Cells - N. A. Kikhtenko; N. A. Bondarenko; N. P. Bgatova; L. A. Oleynik; O. V. Poveshchenko; A. Zh. Fursova; P. G. Madonov (Безопасность и риск фармакотерапии, 2021)
Currently, there are no efficacious, all-purpose antiviral medicines for the treatment of ocular surface infections caused by viruses. At the same time, type III interferons demonstrate high potency for histological barriers, such as the conjunctiva. Modification of protein molecules in native products can significantly improve their pharmacodynamic properties. Thus, it seems reasonable to develop antiviral medicines based on interferon lambda (IFN-λ1) and its pegylated form (PEG IFN-λ1).The aim of the study was to evaluate the in vitro cytotoxic effect of recombinant human IFN-λ1 and its pegylated form on Chang conjunctiva clone 1-5c-4 human conjunctival cells.Materials and methods: PEG IFN-λ1 was obtained by the electron beam immobilisation method. A normal human conjunctival cell line Chang conjunctiva clone 1-5c-4 was used for cell cultivation. The MTT test was used to assess the cytotoxic effect. Cell proliferative activity was studied by measuring microelectrode impedance. Ultrastructural changes were assessed by electron microscopy. Statistical processing was performed using the Statistica 10.0 software package.Results: IFN-λ1 (37 μg/mL) and PEG IFN-λ1 (42 μg/mL) had no significant cytotoxic effect on the human conjunctiva cell culture and the cell proliferative activity. The analysis of ultrastructural changes demonstrated that IFN-λ1 activated metabolic processes in the cells, and PEG IFN-λ1 promoted differentiation and keratinisation of epithelial cells and led to modification of the cell membrane. A ten-fold increase in IFN-λ1 and PEG IFN-λ1 concentration (to 370 μg/mL and 420 μg/mL, respectively) reduced the cell viability by 15–20% as compared to the intact control.Conclusions: the study results demonstrated that IFN-λ1 and PEG IFN-λ1 could be used as active pharmaceutical ingredients in the development of medicines for the treatment of conjunctival viral infections.